Reduction of the Heavy Metal Mercury (Hg) from Paningkaban Gold Mining Tailings, Bayumas, with Ageratum Conyzoides - Althaaf, Nabila Tsabita; Aminatun, Tien; Rakhmawati, Anna; Atun, Sri (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2025)
Gold is a fairly large contributor to Indonesia's foreign exchange. The area that has the potential to have minerals is Banyumas Regency. This area has been indicated to have gold mineral reserves of around 16,000 hectares. Until now, the gold processing process still uses mercury, which produces negative impacts such as post-mining waste containing heavy metal mercury (Hg), which can cause environmental damage. Environmental damage that arises, such as pollution of the soil and water environment, due to the gold bioleaching process that is disposed of without any treatment. One alternative that can be used to overcome this problem is by using hyperaccumulator plants. One plant that falls into the hyperaccumulator category is the bandotan plant (Ageratum conyzoides), because it is often found in gold mining areas contaminated with mercury. Mercury contamination will be absorbed from the environment into the body of Ageratum conyzoides through membranes and converted into less toxic substances. The aim of this research is to determine the ability of the Ageratum conyzoides plant as a phytoremediation agent in reducing mercury metal (Hg) in tailings from Paningkaban Village, Banyumas. There are two treatments, namely the planting media used with 2 kg of tailings soil and 2 kg of planting media mixed with tailings and compost. The mixture ratio between tailings and compost is 1:1. Each treatment, consisting of three replications, was observed using plant growth parameters (plant height and number of leaves), as well as control parameters (edaphic and microclimatic). The results of the research show that the Ageratum conyzoides plant is a phytoremediation agent that can reduce levels of the heavy metal mercury (Hg) in the planting medium of mining tailings soil from Paningkaban Village, because it gives test results of BCF values > 1 and TF < 1, which indicates that the Ageratum conyzoides plant has potential as a phytostabilizing agent.